Overview of Monogenic Forms of Hypertension Combined With Hypokalemia - Lu, Yi-Ting; Fan, Peng; Zhang, Di; Zhang, Ying; Meng, Xu; Zhang, Qiong-Yu; Zhao, Lin; Yang, Kun-Qi; Zhou, Xian-Liang (Frontiers in Pediatrics, 2021)
Hypertension is an important risk factor in many conditions and creates a heavy burden of disease and mortality globally. Polygenic hypertension is the most common form; however, it is increasingly recognized that monogenic hypertension is not rare, especially in patients with electrolyte disorders. Single genetic alterations are associated with plasma volume expansion and catecholamines/sympathetic excess with simultaneously increased potassium excretion in the urine and potassium intracellular shift. Early-onset refractory hypertension and profound hypokalemia are characteristics of monogenic hypertension. However, accumulated evidence shows the existence of phenotypic heterogeneity in monogenic hypertension meaning that, even for mild symptoms, clinicians cannot easily exclude the possibility of monogenic hypertension. Genetic, epigenetic, and environmental factors are all possible mechanisms influencing phenotypic diversity. Genetic sequencing is a precise and efficient method that can broaden the mutant gene spectrum of a disease and is very helpful for understanding the pathophysiology of monogenic hypertension. Genetic sequencing, along with biochemical tests and imaging modalities, is essential for the early diagnosis and targeted management of monogenic hypertension to avoid long-term catastrophic complications.